Toughening of thin ceramic plates using bioinspired surface patterns. (15th October 2016) - Malik, Idris A.; Barthelat, Francois
Highlights: Laser engraving of narrow trenches on the surface of thin alumina plates can guide the propagation of in-plane cracks. The apparent toughness of these ``interfaces'' can be tuned by changing the depth of the trench. The overall fracture toughness of the plate can be improved by engraving transverse interfaces or sinusoidal interfaces. Complex architectured and mechanisms are possible: bio-inspired sutures resembling an interlocking jigsaw generate high toughness, frictional pull-out, and completely transform the way the material deforms and fails in tension. Abstract: High-performance natural materials such as bone, teeth or mollusk shells contain a large volume fraction of minerals to generate stiffness and hardness. They are also packed with weak interfaces, which generate nonlinear deformations and channel cracks into powerful toughening configurations. As a result, these natural materials achieve simultaneous stiffness, hardness and toughness, which are properties which are mutually exclusive in engineering materials. Following these concepts, we have engraved trenches with controlled patterns and depth in thin plates of aluminum oxide. The trenches can guide propagating cracks, which we use to implement toughening mechanisms and unusual deformation mechanisms. We present fracture results on samples with transverse interfaces and sinusoidal interfaces. We also explore interlocking-jigsaw like interfaces, which dissipate the most energy and produce the highest toughness. These interfaces also profoundly change the way the material deform in tension, by introducing controlled non-linear deformations accompanied with geometric hardening and frictional pullout, in an otherwise all-brittle material.